The Flavour of Memories, Survival Tactics and Taste Memory of the Holodomor Victims (1932-1933) (2023)
The article analyses the food practices of the farmer population located in the forest-steppe region of Ukraine during the artificial famine that took place between the fall of 1932 and the spring of 1933, known as the Holodomor. For the study, forty archived testimonies were analysed from a phenomenological perspective to understand the meaning survivors gave to the ingestion of plant and animal-based substitute foods. The study identified that during and after the famine, the Ukrainian farmer population ceased to consider eating as a social and political event that kept them united under a shared national consciousness, and instead became the means by which they obtained the energy necessary for physical stability.